Targeting the Nerve Growth Factor Signaling Impairs the Proliferative and Migratory Phenotype of Triple-Negative Breast Cancer Cells - Di Donato, Marzia; Galasso, Giovanni; Giovannelli, Pia; Sinisi, Antonio A.; Migliaccio, Antimo; Castoria, Gabriella (Frontiers in Cell and Developmental Biology, 2021)
Triple-negative breast cancer is a heterogeneous disease that still lacks of specific therapeutic approaches. Systemic chemotherapy and/or radiotherapy represent, indeed, the most commonly used treatments for these cancers. Therefore, identification of new biomarkers, predictive of the disease’s aggressiveness and pharmacological response represents a challenge toward a more tailored approach in clinical management of patients. Nerve growth factor, initially identified as a key factor for neuronal survival and differentiation, has captured for a long time the interest of neurobiologists. However, it turned out to be a multifaceted molecule with pleiotropic effects in quite divergent cell types, including cancer cells. Many solid tumors exhibit derangements of nerve growth factor and its receptors, including the tropomyosin receptor kinase A. This receptor is expressed in triple negative breast cancers, although its role in pathogenesis and aggressiveness of this disease is still under investigation. We now report that triple negative breast cancer-derived MDA-MB-231 and MDA-MB-453 cells express appreciable levels of the tropomyosin receptor kinase A and release biologically active nerve growth factor. Once activated by the neurotrophin, tropomyosin receptor kinase A positively affects migration, proliferation and growth in 3D models of triple negative breast cancer cells. This latter effect might also occur through the nerve growth factor-induced release of matrix metalloproteinase 9, which contributes to the reorganization of the extracellular matrix. Specific inhibition of the tropomyosin receptor kinase A by GW441756 reverses all these responses. Co-immunoprecipitation experiments in NGF-treated MDA-MB-231 cells show that nerve growth factor triggers the assembly of TrkA/1-integrin/FAK/Src complex and activates several downstream effectors. GW441756 inhibits the complex assembly induced by nerve growth factor as well as the activation of its dependent signaling. Taken together, these data boost the importance of nerve growth factor/tropomyosin receptor kinase A pathway in triple negative breast cancer, thus suggesting new hints in the diagnostic and clinical management of patients.